2004
DOI: 10.1159/000076256
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Artesunate on Angiogenesis and on Expressions of Vascular Endothelial Growth Factor and VEGF Receptor KDR/flk-1

Abstract: Artesunate (ART) is a semi-synthetic derivative of artemisinin extracted from the plant Artemisia annua is a safe and effective antimalarial drug. In the present investigation, ART was found also to inhibit angiogenesis in vivo and in vitro. The anti-angiogenic effect in vivo was evaluated in nude mice by means of human ovarian cancer HO-8910 implantation and immunohistochemical stainings for microvessel (CD31), vascular endothelial growth factor (VEGF) and VEGF receptor KDR/flk-1. Tumor growth was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 36 publications
3
62
1
2
Order By: Relevance
“…We and others have described antiangiogenic effects of ARS in vitro and in vivo. [25][26][27][28][29][30][31][32] ART strongly reduced neovascularization of Matrigel plugs injected under the skin of mice when administered with the drinking water. No apoptotic effects on endothelial cells were observed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We and others have described antiangiogenic effects of ARS in vitro and in vivo. [25][26][27][28][29][30][31][32] ART strongly reduced neovascularization of Matrigel plugs injected under the skin of mice when administered with the drinking water. No apoptotic effects on endothelial cells were observed.…”
Section: Discussionmentioning
confidence: 97%
“…27 ART and dihydroARS reduced the expression of the two major VEGF receptors, Flt-1 and Table 1 THBS1 TGFB2 PLAU AXL CYR61 FGF2 FGF2 EphA2 MPDZ IL6ST COL18A1 NID2 FN1 MMP9 BMP1 ANG PIN BMPR2 DVL3 MMP11 GJA4 COL4A2 HIF1A NOS2A ABCG1 COL1A2 VEGFC F3 TFPI2 NRCAM EFEMP1 EFEMP1 SNB- Angiogenesis-related genes predict cellular response to artemisinins L Anfosso et al induction of cellular apoptosis and inhibition of expression of VEGF receptors. 28,29,31 In addition to ARSs, other sesquiterpene lactones, such as costunolide also inhibit the VEGFR KDR/Flk-1 signaling pathway. 47 It merits further investigation to analyze, whether the correlations between gene expression and GI 50 values for ARSs found in the present investigation are events downstream of the inhibition of the VEGF ligand/receptor system or whether other angiogenic regulators are also causative affected by these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was inspired by anticancer studies conducted with AS (Efferth et al, 2001;Chen et al, 2003;2004b GD 1-6 GD 7-13 GD 9.5, 10.5 GD 6-15 GD 6-17 GD 10 GD 10 GD10 GD 10 GD 11 GD 6-15 GD 6-15 GD 11 GD 6-13 FRD50 or 100 = drug dose induces 50% or 100% fetus re-absorbed; GD = gestation day (The day of mating was defined as day 0 of gestation.) * The severe toxic effects were detected in the animals treated with AS after single or multiple intramuscular, intravenous or subcutaneous injections.…”
Section: Embryotoxicity Of As/dha Caused By Defective Vasculogenesis/mentioning
confidence: 99%
“…Recently, several studies showed that ART could inhibit the growth of various carcinoma cell lines [1][2][3] and suppress tumor cell proliferation by inducing apoptosis, 4 indicating that ART may be a promising novel candidate for leukemia therapy. However, a variety of lines of evidence indicate that ART inhibited cell proliferation in a dose-dependent manner, and a high concentration of ART induced embryo toxicity, [5][6][7] reversible renal damage toxicity, 8 and toxicity to bone development, 9 which limit the usefulness of ART. To minimize side effects associated with dosage during chemotherapy, a promising approach is to combine a conventional chemotherapy with new strategies to maximize efficacy of tumor treatment through inducing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%